Development of a Novel Restrictive Medium for Monascus Enrichment From Hongqu Based on the Synergistic Stress of Lactic Acid and Ethanol - Zhou, Kangxi; Wu, Li; Chen, Guimei; Liu, Zhibin; Zhao, Xinze; Zhang, Chen; Lv, Xucong; Zhang, Wen; Rao, Pingfan; Ni, Li (Frontiers in Microbiology, 2021)
Excellent Monascus strain is an important prerequisite for producing high-quality Hongqu which has been used as food coloring, wine starters and food additives. However, the isolation of Monascus pure culture from Hongqu samples is time-consuming and laborious because it is easily interfered by other microorganisms. Therefore, the development of restrictive medium for Monascus enrichment from Hongqu is of great significance for the preparation and screening of excellent Monascus strains. Results of this study showed that Monascus has good tolerance to lactic acid and ethanol. Under the conditions of tolerance limits (7.5% lactic acid (v/v) and 12.0% ethanol (v/v)), Monascus could not grow but it still retained the vitality of spore germination, and the spore activity gradually decreased with the increasing concentrations of lactic acid and ethanol. More interestingly, the addition of lactic acid and ethanol significantly changed the microbial community structure in rice milk inoculated with Hongqu. After response surface optimization, Monascus could be successfully enriched without the interference of other microorganisms when 3.98% (v/v) lactic acid and 6.24% (v/v) ethanol were added to rice milk simultaneously. The optimal enrichment duration of Monascus by the restrictive medium based on the synergistic stress of lactic acid and ethanol is 8h~24h. The synergistic stress of lactic acid and ethanol had no obvious effects on the accumulation of major metabolites in the progeny of Monascus, and was suitable for the enrichment of Monascus from different types of Hongqu. Finally, the possible mechanisms on the tolerance of Monascus to the synergistic stress of lactic acid and ethanol were preliminarily studied. Under the synergistic stress of lactic acid and ethanol, the cell membrane of Monascus defends against lactic acid and ethanol into cells to some extent, and the superoxide dismutase, catalase and glutathione peroxidase activities of Monascus were higher than those of other fungi, which significantly reduced the degree of lipid peroxidation of cell membrane, while secreting more amylase to make reducing sugars to provide the cells with enough energy to resist environmental stress. This work has great application value for the construction of Monascus strain library and the better development of its germplasm resources